2011
DOI: 10.1016/j.cpr.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity, the menstrual cycle, and panic disorder: A putative neuroendocrine and psychological interaction

Abstract: The 2:1 female-to-male sex difference in the prevalence of Panic Disorder (PD) suggests that there is a sex-specific vulnerability involved in the etiology and/or maintenance of this disorder. The purpose of this paper is to present a new conceptual model, which emphasizes the interaction between a cognitive vulnerability for PD, anxiety sensitivity, and the effects of progesterone and its metabolite, allopregnanolone, on behavioral and physiological responses to stress during the premenstrual phase. This inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 93 publications
0
58
0
3
Order By: Relevance
“…Almost all of the female probands had been on hormonal contraceptives during participation in the present study. The actual hormonal status, however, was not considered in the present study, which might have introduced a potential confounder based on case reports suggesting oral contraceptives to potentially induce panic attacks (Deci et al, 1992;Ushiroyama et al, 1992) and animal as well as human studies providing evidence for gonadal hormones and menstrual cycle to modulate AS (Nillni et al, 2011;Toufexis et al, 2006). Furthermore, the functional relevance of the silent ADOR-A2A 1976T4C polymorphism is still unknown and therefore the mechanism by which this variant might confer susceptibility to anxiety remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the female probands had been on hormonal contraceptives during participation in the present study. The actual hormonal status, however, was not considered in the present study, which might have introduced a potential confounder based on case reports suggesting oral contraceptives to potentially induce panic attacks (Deci et al, 1992;Ushiroyama et al, 1992) and animal as well as human studies providing evidence for gonadal hormones and menstrual cycle to modulate AS (Nillni et al, 2011;Toufexis et al, 2006). Furthermore, the functional relevance of the silent ADOR-A2A 1976T4C polymorphism is still unknown and therefore the mechanism by which this variant might confer susceptibility to anxiety remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to species differences; however, progesterone has been shown to suppress HPA axis activity via conversion to its metabolite allopregnanolone (Biggio, Pisu, Biggio, & Serra, 2014). In fact, a number of studies have reported anxiolytic properties of allopregnanolone (Nillni, Toufexis, & Rohan, 2011; Pibiri, Nelson, Guidotti, Costa, & Pinna, 2008; D. J. Toufexis, Davis, Hammond, & Davis, 2004).…”
Section: Gonadal Hormones Stress and Fear Extinctionmentioning
confidence: 99%
“…The initiation of fluctuating sex steroid hormones over the menstrual cycle in women [see review (Nillni et al, 2011)] could be an important factor that contributes to the higher rates of PA and PD in women, but other factors such as early life stress or higher incidence of trauma such as sexual abuse or domestic violence in women could also account for this vulnerability. Evidence supporting a hormonal contribution includes a study demonstrating that female PD subjects with agoraphobia reported experiencing premenstrual exacerbations in anxiety symptoms, a pattern which could increase the rate of ePAs and contribute to the development of agoraphobia in these subjects (Breier et al, 1986).…”
Section: Section 3 – Empirical Evidence For Biological Basis Of Recurmentioning
confidence: 99%